The Arrangement Concept and the Energy Potential of the Vapor Compression Heat and Cooling Supply Based on a Binary Low-Temperature Source - V. D. Petrash; O. I. Khomenko; D. V. Basist; A. Ujma (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The combined use of low-potential soil heat and air flows in heat pump heat supply systems allows for its regulated redistribution in the processes of customers’ consumption. Herewith, the intensity of energy extraction by the soil heat exchanger decreases, excess heat is accumulated with a decrease in the depth of wells, and the costs of installing and operating probe heat exchangers are also reduced. An improved version of the conceptual arrangement of a vapor compression system for heat and cool supply of buildings based on the integrated heat of soil and ventilation air has been developed. Its distinguished features are the possibility of automatic redistribution of generated heat flows in the subsystems of customers’ heat consumption and accumulation of excess part in the soil mass. When the system is operating in the warm season with the extraction of heat only for hot water supply, there is a more intensive accumulation of excess heat of the ventilation air in the soil mass, which restores its temperature in the accumulation mode for further use with the coming of the heating period. Multifactor analytical dependences of the heat flows of the main equipment have been established, taking into account the initial parameters and operating conditions of the structural subsystems for the extraction, transformation and consumption of heat, which are the basis for determining the energy potential of vapor compression heat and cold supply using a binary low-temperature source.